Spectrum Sharing Approach: Turkey Model Proposal - Özkoç, Esma Ergüner; Gebiç, Gürkan (Law, State and Telecommunications Review, 2024)
[Purpose] Spectrum is a scarce and valuable national resource. With 5G, it is predicted that the demand for spectrum will increase gradually. In order to overcome the increasing data traffic problem and connection needs, the spectrum should be used as efficiently as possible. This paper aims to develop a new perspective on spectrum management in Turkey, and the applicability of spectrum sharing applications in Turkey has been investigated. Suggestions were made regarding the changes that can be made in the current legislation. [Methodology/Approach/Design] Within this study, interviews were held with the three leading mobile operators in Turkey through focus group discussion, and evaluations were made about the approach of Turkey’s mobile communication sector to the subject. In addition, innovative spectrum management practices in Europe and United States (US) regarding the emerging spectrum sharing approach were examined. The current practices of European countries were presented in the semi-structured interview via e-mail. [Findings] This paper provides opinions of Turkish leading mobile operators about spectrum sharing, current EU and US practices, and necessary changes in Turkish legislation to enable spectrum sharing. A new perspective on spectrum management in Turkey has been developed, and the applicability of spectrum sharing applications in Turkey has been investigated. Suggestions were made regarding the changes that can be made in the current legislation. [Practical Implications] What outcomes and implications for practice, applications and consequences are identified? How will the article impact on society, business, or enterprise? What changes to practice should be made as a result of this research? What is the legal or economic impact? [Originality/Value] This paper fulfills the need for originality and presents new knowledge about spectrum sharing in Turkey's telecommunication sector.